Effect of Distributed and Instructional Leadership of Chinese School Principals on the Job Satisfaction of Teachers: A Conceptual Paper - Xin, Zhao; Tahir, Suhaidah Binti (South Asian Journal of Social Sciences and Humanities, 2024)
School principals’ leadership behaviours influence the job satisfaction of the teacher, which in turn, defines the effectiveness of the school climate. Therefore, it is crucial to know how the leaderships styles, specially the distributed and instructional leadership, affect the job satisfaction of the teachers in the Chinese school context. So, the aim of the study is to analyse the effect of distributed and instructional leadership of Chinese school principals on the job satisfaction of teachers along with the mediating roles of reward, motivation, and effectiveness. In order to achieve the aim, the study adopted a “review-style” research method and explored the relevant past literature. The researcher confined the time frame from 2019 to 2024 to include the most recent studies and the theses, books, and discussions were not utilized as they did not fit into the standard of research articles. In the context of educational policy and school management practices worldwide, the implications of this study are significant. Therefore, suitable leadership interventions would improve teachers’ work satisfaction and consequently, the students’ achievements.